Ancient Caesarea : conservation and development of a Heritage Site - Fuhrman-Naaman, Yael; Porath, Y. (Israel Antiquities Authority, 2017)
Caesarea and its artificial harbor were constructed on the Mediterranean Sea, midway between 'Akko and Yafo (Jaffa). This location created a magnificent meeting point of nature and landscape on the one hand, and of cultural heritage on the other, albeit at the cost of exposing the site to accelerated processes of weathering and destruction. The Israel Antiquities Authority undertook the task of saving the ruins of Caesarea and turning them into a tourist heritage site. Archaeological excavations, conservation and reconstruction works, alongside modern use of ancient and historical buildings at.